HORMONAL AND CHEMICAL EVALUATION OF PCOS IN AL-NAJAF, IRAQ - Al-Mansoori, Hassan Ali (American Journal of Public Health and Epidemiology (AJPHE), 2023)
Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine and metabolic disorder affecting up to 17.8% of women. It is distinguished by hyperandrogenism, irregular menstrual cycles, and the presence of polycystic ovaries. Hyperandrogenism is a key defining characteristic of PCOS, with around 80% of diagnosed cases meeting the National Institute of Health (NIH) consensus criteria for elevated androgen levels. Hyperandrogenemia is the underlying cause of the distressing signs and symptoms associated with PCOS, including hirsutism, male-pattern baldness, and irregular or absent ovulation. The precise etiology of PCOS remains elusive, but it is closely linked to increased androgen secretion, suggesting aberrant folliculogenesis and steroidogenesis as primary contributors to the condition. Early diagnosis of PCOS during adolescence is of paramount importance, given its significant association with infertility, obesity, dyslipidemia, diabetes mellitus, cardiovascular disease, and endometrial hyperplasia in later life. Obese individuals with PCOS often exhibit distinctive lipid profiles, characterized by elevated plasma triglycerides and decreased lipoprotein cholesterol concentrations, adding to the complexity of the syndrome. Moreover, PCOS patients may face dyslipidemia due to factors such as obesity, diabetes mellitus, cigarette smoking, and genetic predisposition.